Clothing Thermal Insulation of Infant in Stroller Relating to Evaluation of Thermal Environment of Infant - Kurazumi, Yoshihito; Fukagawa, Kenta; Sakoi, Tomonori; Yamashita, Ken; Naito, Akie; Imai, Motoe; Yamato, Yoshiaki; Kondo, Emi; Tsuchikawa, Tadahiro (European Journal of Applied Sciences, 2023)
The clothing thermal insulation for individual clothing ensembles of infant and strollers has been clarified. However, the clothing thermal insulation for the combination of them has not been measured at all. The purpose of this study is to examine the typical values of human factors such as the clothing area factor and clothing thermal insulation of an infant in a stroller. As typical clothing ensembles, seasonal combinations of infant clothing with a stroller were selected. The stroller was treated as part of the infant’s clothing. The clothing area factors were measured by using the photographic method. The clothing thermal insulations were measured by using an infant’s thermal manikin. The typical clothing area factor of an infant in a stroller is 3.67 for summer clothing, 3.75 for mid-season clothing, and 4.19 for winter clothing. The typical clothing thermal insulation of an infant in a stroller is 1.23 clo for summer, 1.39 clo for mid-season, and 1.97 clo for winter. The stroller was shown to significantly affect the body heat balance between the infant and the thermal environment.